PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN DENGAN CAPITAL STRUCTURE SEBAGAI VARIABEL MODERASI (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023) - Rahmawati, Anisha; Mutmainah, Siti (Diponegoro Journal of Accounting, 2024)
This study aims to examine the impact of GCG on firm performance with capital structure as a moderating variable. The independent variable in this study is GCG, measured through independent commissioners, the audit committees, the board of directors, institutional ownership, and managerial ownership. The dependent variable used is company performance, measured by ROA. This study also involves capital structure as a moderating variable, measured using DAR. The study population consists of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period of 2019-2023. The sample for the study was determined using purposive sampling, resulting in a total sample of 165 companies over five years. Hypothesis testing was conducted using multiple regression analysis and moderated regression analysis. The results of this study indicate that the presence of independent commissioners, institutional ownership does not have a significant impact on company performance, the presence of the audit committee, board of directors, managerial ownership has a significantly positive impact on company performance, the presence of capital structure does not moderate the effect of independent commissioners, audit committee, board of directors, institutional ownership, managerial ownership on company performance.